Development of the Droplet Digital PCR to Detect the Teliospores of Tilletia controversa Kühn in the Soil With Greatly Enhanced Sensitivity - Liu, Jianjian; Li, Chao; Muhae-Ud-Din, Ghulam; Liu, Taiguo; Chen, Wanquan; Zhang, Jianmin; Gao, Li (Frontiers in Microbiology, 2020)
Background and aims The dwarf bunt disease of wheat is caused by Tilletia controversa Kühn. This pathogen is primarily involved in the stunted growth of wheat and affects seed quality. Many countries in the world have therefore imposed quarantine bans to prevent the spread of T. controversa. Morphological observations are the main method of detecting teliospores in soil, as T. controversa is a soilborne pathogen. However, this is not an accurate approach and is a lengthy and laborious process; this method is thus unable to quickly meet the demand for detection of teliospores in the soil. Methods We compared PCR, real-time PCR and droplet digital PCR (ddPCR) for the qualitative and quantitative measurement of the teliospores of T. controversa in soil. Results We suggest the use of droplet digital PCR (ddPCR), which was demonstrated to have the most sensitive detection at 2.1 copies/μL. In contract, SYBR Green I real-time PCR could detect 7.97 copies/μL of T. controversa in soil, and this sensitivity was 100 times more sensitive than that of simple PCR. Conclusion This study was the first report using ddPCR techniques to detect T. controversa teliospores in soil with greatly enhanced sensitivity.